THE TEACHING OF ORAL COMMUNICATION SKILLS IN THE ENGLISH CURRICULUM IN PRIMARY SCHOOLS IN KENYA - Syomwene, Anne (European Scientific Journal, ESJ, 2013)
The English curriculum is significant in schools in Kenya because of the importance of English Language as the medium of instruction in schools in Kenya from upper primary school and beyond. Further, English is the official language in Kenya. Oral communication skills which comprise listening and speaking skills form the backbone to the teaching of English. They facilitate the acquisition of other language skills: reading and writing. This paper is a report on a study on the teaching of oral communication skills in English that was undertaken in Nandi North district, Kenya in the year 2009. The study investigated the teaching of oral communication skills in the English curriculum in Primary schools in Kenya. The study adopted Vygotsky’s (1978) theory of social interaction. It utilized a qualitative research approach with a heuristic methodology. An exploratory research design was used. The research population consisted of primary school teachers teaching English in upper primary classes and standard six pupils. Data was collected using structured and focused group interview schedules, observation checklists and document analysis. The study delved on two objectives: To find out the kind of learning activities that the teachers selected for oral communication lessons; To find out the methods that teachers used to convey the meaning of new language items during oral communication lessons. This paper is a discussion of the findings, conclusions and recommendations of this study.